Santiago's Strife For Success In Paolo Coelho's The Alchemist Novel (1992): An Individual Psychological Approach - Farizi, Ilmam Dani; , Drs. H. Abdillah Nugroho, M.Hum; , Dr.Phil. Dewi Candraningrum (2013)
The major problem of this study is how Santiago's strife for success reflected in Paolo Coelho's The Alchemist novel. The objective of this study is to analyze the novel based on its structural elements and to analyze the novel based on individual psychological approach as major theory and strife for success as issue. In analyzing The Alchemist novel, the researcher uses qualitative method and feminist approach. The data sources consist of primary data and secondary data sources. The primary data source is the novel The Alchemist itself and the secondary data sources are the other sources related to the analysis of the object and issue. The method of the data collection is descriptive analysis. The first result of the study in structural analysis shows that The Alchemist is simple fiction based on portion for structural elements. The second result in personality analysis, Santiago's strive for success is the journey to discover personal legend or self destiny. In process to strive for success, treasure as symbol Santiago's final goals is bringing individual experience which being analyzed using six basic principles of Adler's Individual psychological approach. The result shows that Santiago striving for spiritual and psychological experiences is precious for livehood.